Size matters? Impact evaluation of business development grants on SME performance - Stjepan Srhoj; Michael Lapinski; Janette F. Walde (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2019)
Many international organisations emphasize the need of public grant schemes evaluations. An evaluation provides the opportunity to assess the socio-economic impact achieved by the grant and allows for a refinement of such policy instruments in order to make public funding more effective in achieving the objectives. In this paper, we investigate the effects of a business development grant scheme. More specifically we question whether firms' performance measures increased after participating in this grant scheme. Methodically, we match grant receiving firms with grant non-receivers and estimate the average treatment effect on the treated using a two way fixed effects regression. Our results point towards a positive effect of the grant scheme, which is particularly evident for firms of smaller size. Our estimated dose-response functions show that the share of grant amount in firm profits needs to be high enough for the grants to be effective. According to back-of-the envelope analysis, benefits outweigh the direct scheme costs.
Keywords: C21; G01; H23; H50; O38; 330; business development grants; policy evaluation; two-way fixed effects regression; matching; heterogeneous treatment effects; dose-response-function